Poincaré Inequalities for Composition Operators with Lφ-Norm - Ru Fang (Abstract and Applied Analysis)
We establish the Poincaré-type inequalities for the composition of the homotopy operator, exterior derivative operator, and the projection operator with Lφ-norm applied to the nonhomogeneous A-harmonic equation in Lφ(Ω)-averaging domains.